Locality in the acquisition of object A’-dependencies: insights from French - Anamaria Bentea; Stephanie Durrleman (Glossa, 2021)
Children’s difficulties with dependencies involving movement of an object to the left periphery of the clause (object relative clauses/RCs and wh-questions), have been explained in terms of intervention effects arising when the moved object and the intervening subject share a lexical N feature (Friedmann, Belletti & Rizzi 2009). Such an account raises various questions: (1) Do these effects hold in the absence of a lexical N feature when the object and the intervener share other relevant features? (2) Do phi-features with a semantic role modulate such effects? (3) Does the degree of feature overlap determine a gradience in performance? We addressed these in three sentence-picture matching studies with French-speaking children (4;8 to 6;3), by assessing comprehension of (1) subject and object RCs headed by the demonstrative pronouns celui/celle and matching or mismatching in number; (2) object RCs headed by a lexical N and matching or mismatching in animacy; (3) object who- and which-questions. Our results show that mismatches in number, not in animacy, enhance comprehension of object RCs, even in the absence of a lexical N feature, and confirm previous findings that object who-questions yield better comprehension than object which-questions. Comparing across studies, the following gradation emerges with respect to performance accuracy: disjunction > intersection > inclusion. The global interpretation of these findings is that fine-grained phi-features determining movement are both sufficient and necessary for locality, and the degree of overlap of these features can capture the pattern of performance observed in children, namely higher accuracy as featural differences increase.